Assistance and Establishment of an Anti-Corruption Legal Clinic in Puguh Village, Boja District, Kendal Regency - Anis Widyawati; Indung Wijayanto; Dian Latifiani; Ardi Sirajudin Ra’uf; Annisa Suci Rosana (Jurnal Dedikasi Hukum, 2021)
The cause of corruption in village funds is due to the lack of competence of village officials, lack of transparency and lack of government and community supervision as well as superior intervention in the implementation of physical activities that are not according to planning. A joint commitment from the Puguh Village Government and the community is needed in alleviating corruption at the village level. This paper describes and analyzes various efforts to increase anti-corruption awareness for the community and the Puguh Village Government. The method used in this program includes three things, namely: (1) exploratory; (2) topical; (3) evaluation and monitoring. The service team embodies a commitment to answer problems by establishing an anti-corruption legal clinic with programs including counseling on anti-corruption from the KPK Education Center related to transparent and corruption-free village fund management, computer and internet training from UPTTIK UNNES for the use of an online system in managing village funds and online marketing of village products, as well as assistance in resolving legal cases that occur in the community through a legal aid study center.   Pendampingan dan Pendirian Klinik Hukum Anti Korupsi di Desa Puguh, Kecamatan Boja, Kabupaten Kendal. Penyebab korupsi dana desa adalah adanya intervensi atasan dalam pelaksanaan kegiatan fisik yang tak sesuai perencanaan, tidak adanya transparansi dan kurangnya pengawasan pemerintah dan masyarakat. Komitmen bersama dari Pemerintahan Desa Puguh dan masyarakat dibutuhkan dalam mengentaskan korupsi di tingkat desa. Tulisan ini mendeskripsikan dan menganalisis berbagai upaya dalam meningkatkan kesadaran anti korupsi bagi masyarakat dan Pemerintahan Desa Puguh. Metode yang digunakan dalam program ini  meliputi  tiga  hal,  yaitu:  (1) eksplorasi; (2) topikal; (3) evaluasi dan pemantauan. Tim pengabdi mewujudkan komitmen untuk menjawab permasalahan dengan membentuk klinik hukum anti korupsi dengan program antara lain penyuluhan mengenai anti korupsi dari Pusat Edukasi KPK terkait pengelolaan dana desa yang transparan dan bebas korupsi, pelatihan komputer dan internet dari UPTTIK UNNES untuk penggunaan sistem online dalam pengelolaan dana desa dan pemasaran produk desa secara online, serta pendampingan penyelesaian perkara hukum yang terjadi di masyarakat melalu pusat kajian bantuan hukum.